Symposium 3: Stage on the page: Trying out the metaphor of Japanese Noh and Kabuki theatre as a way to explore text based activities in a Virtual Learning Environment - Thomas, Hilary (Proceedings of the International Conference on Networked Learning, 2012)
My research challenge is to find a way to understand relationships mediated through a text based Virtual Learning Environment for a distance learning Masters programme in Creative Writing, and to understand in what way these relationships support - or don’t support - the development of those students towards their learning goals. In my research I combine concepts and approaches that are rooted in Sociology, Psychology and Literary Theory/Creative Writing. The focus of this paper is based in work in progress on ways of thinking about those online relationships and how as a researcher to observe and understand them. I have harnessed the use of a metaphor of Japanese Kabuki and Noh theatres to help me structure my thinking and to play with ideas drawn from the different disciplines with which I approach my research. My metaphor is built on that of Goffman (1969), with performance and stage serving as a way to understand the presentation of self. My refinement of Goffman’s metaphor allows me to explore the issues associated with self presentation in this asynchronous online environment where interaction is apparently more measured and controlled. As with Goffman there are criticisms to be made of the dramaturgical analogy concerning how much conscious control there is of behaviour, but these criticisms become integral to my exploration of this environment, throwing up questions about communication and what it is to perform. My attention turns to the audience. In my research of this online environment I see myself as part of the audience. I use the metaphor to explore the role of a researcher in this context, highlighting issues of ontology and epistemology that colour how I regard ’the show’. However, in pursuing an approach informed by grounded theory and from a ’relational psychoanalytic’ stance, I find myself shifting position in the dramaturgical analogy. I recognise my interpretations shaping and influencing the way I collect and understand data but I also recognise that I am instrumental in generating some of that data through the relationships between me and my interviewees. I need to regard not only my own responses and interpretations as part of my research data, but also to observe the process of intersubjectivity between me and my research participants. In turn I need also to consider the process of intersubjectivity between me and my own audience, you the reader.